Effect of Eu doping concentration on fluorescence and magnetic resonance imaging properties of Gd2O3:Eu3+ nanoparticles used as dual-modal contrast agent. (3rd August 2018) - Deng, Huawei; Chen, Fei; Yang, Chuan; Chen, Min; Li, Li; Chen, Dihu
Abstract: Europium-doped gadolinium oxide (Gd2 O3 :Eu 3+ ) nanoparticles (NPs) with favorable properties for use in fluorescence imaging (FI) and magnetic resonance imaging (MRI) dual-modal contrast agent has attracted intense attention in biomedical applications. However, limited information is available on balancing FI and MRI by adjusting doping concentrations. In this study, Gd2 O3 :Eu 3+ NPs with various Eu 3+ doping concentrations were prepared by the facile and general technique of laser ablation in liquid (LAL). The influence of Eu 3+ -doping concentration on fluorescence properties and longitudinal relaxivity were investigated. The optimum Eu 3+ -doping concentration with both high fluorescence properties and longitudinal relaxivity was determined to be 5%. The characterization of the structure, morphology, and composition shows that these NPs possess good crystallinity and excellent dispersibility. These results show that Gd2 O3 :Eu 3+ NPs prepared by LAL are promising candidates for highly efficient FI and MRI dual-modal contrast agents.